Diurnal rhythms in psychological reward functioning in healthy young men: 'Wanting', liking, and learning. (7th February 2017) - Byrne, Jamie E. M.; Murray, Greg
ABSTRACT: A range of evidence suggests that human reward functioning is partly driven by the endogenous circadian system, generating 24-hour rhythms in behavioural measures of reward activation. Reward functioning is multifaceted but literature to date is largely limited to measures of self-reported positive mood states. The aim of this study was to advance the field by testing for hypothesised diurnal variation in previously unexplored components of psychological reward: 'wanting', liking, and learning using subjective and behavioural measures. Risky decision making (automatic Balloon Analogue Risk Task), affective responsivity to positive images (International Affective Pictures System), uncued self-reported discrete emotions, and learning-contingent reward (Iowa Gambling Task) were measured at 10.00 hours, 14.00 hours, and 19.00 hours in a counterbalanced repeated measures design with 50 healthy male participants (aged 18–30). As hypothesised, risky decision making (unconscious 'wanting') and ratings of arousal towards positive images (conscious wanting) exhibited a diurnal waveform with indices highest at 14.00 hours. No diurnal rhythm was observed for liking (pleasure ratings to positive images, discrete uncued positive emotions) or in a learning-contingent reward task. Findings reaffirm that diurnal variation in human reward functioning is most pronounced in the motivational 'wanting' components of reward.